2021
DOI: 10.1007/s10461-021-03334-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Sexual Behavior and Psychosocial Functioning in a Clinical Sample of Men who have Sex with Men Using HIV Pre-exposure Prophylaxis

Abstract: The purpose of this study was to evaluate the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on sexual behavior, mental health, and substance use among men who have sex with men (MSM) engaged in pre-exposure prophylaxis (PrEP) care. Generalized linear mixed models and logistic mixed-effect models examined change over time for number of sexual partners, mood, and alcohol consumption. From February 29, 2020 to July 31, 2020, 177 MSM actively engaged in PrEP care were evaluated. The median age was 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…A study of 177 MSM in Rhode Island, USA found that men reported an average of 2·60 fewer sexual partners (95% CI 4·04 -1·40) during the pandemic compared to pre-COVID-19. 35 We observed rapid growth in PEP prescriptions from April through December 2020. In addition, we found that the decline in PEP prescriptions during the COVID-19 pandemic occurred primarily in people aged 50 years and younger, which may be because older adults are less adaptive to this unconventional and underutilized HIV prevention measure in China.…”
Section: Discussionmentioning
confidence: 82%
“…A study of 177 MSM in Rhode Island, USA found that men reported an average of 2·60 fewer sexual partners (95% CI 4·04 -1·40) during the pandemic compared to pre-COVID-19. 35 We observed rapid growth in PEP prescriptions from April through December 2020. In addition, we found that the decline in PEP prescriptions during the COVID-19 pandemic occurred primarily in people aged 50 years and younger, which may be because older adults are less adaptive to this unconventional and underutilized HIV prevention measure in China.…”
Section: Discussionmentioning
confidence: 82%
“…There are two possible explanations for this difference; the first is that we asked about chemsex practice only during the most recent intercourse with a man; this may have led to the proportion of chemsexers being underestimated. The second is related to the period covered by our survey (i.e., first French lockdown) where sexual practices decreased considerably ( Holloway et al, 2021 ; Rogers et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on MSM investigating the risks associated with lockdown measures and other COVID-19-related consequences highlighted a reduction in HIV consultations and interruption in PrEP and HIV testing ( Santos et al, 2021 ). Unsurprisingly, others highlighted reductions in sexual intercourse by MSM in many countries; more specifically reductions ranged from 2.6 fewer sexual partners in patients interviewed in a PrEP clinic in the United States ( Rogers et al, 2022 ) to a sixfold decrease in sexual intercourse with steady partners participating in an online survey conducted in more than 100 countries ( Holloway et al, 2021 ). The latter study also demonstrated that social distancing negatively affected both the quality of sexual life of some MSM and anxiety levels.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent investigations have shown that more than half of men who have sex with men (MSM) reported a reduction in the number of condomless sexual intercourse, multiple sex partners, and casual sex partners at the beginning of the implementation of COVID restrictions than before COVID restrictions worldwide. 33–38 A recent study including 10,654 MSM from 20 countries also indicated that more stringent responses were associated with decreased accesses to HIVST. 8 Second, express service is the key to deliver HIVST kits from online merchants to purchasers, which was severely disrupted at the beginning of the implementation of COVID restrictions.…”
Section: Discussionmentioning
confidence: 99%